Avaliação do estado de conservação de nascentes no município de Sinop-MT - Müller, Eliana Aparecida dos Reis (2021)
Water is a natural resource of high economic value and essential for survival, but this environmental resource is vulnerable due to various impacts, such as deforestation and urban expansion. Thus, the objective of this work was to characterize the conservation status of 716 headwaters in the municipality of Sinop/MT and to evaluate the land use in its surroundings. The headwaters were spatialized only by remote sensing. The quantification of land use in its surroundings was carried out within an 50m buffer, where landscape attributes were extracted. The present work generated an environmental impact index in the headwaters. For this, a macroscopic diagnosis of the headwaters was performed, through remote sensing images, and each attribute evaluated received a score (from 1 to 4 points) to assess the degree of preservation of the headwaters. Final scores reflect the level of preservation of the headwaters. Based on the results and information obtained, it was observed that 72.49% of the headwaters are in a good state of conservation, 13.55% regular, 7.96% excellent, 3.35% poor, and 2.65% in bad state of conservation. As a direct application of this study, it is expected that these results can guide government actions and long-term studies for the recovery and preservation of local water resources.